Storage-Induced Micro-Erythrocytes Can Be Quantified and Sorted by Flow Cytometry - Marin, Mickaël; Peltier, Sandy; Hadjou, Youcef; Georgeault, Sonia; Dussiot, Michaël; Roussel, Camille; Hermine, Olivier; Roingeard, Philippe; Buffet, Pierre A.; Amireault, Pascal (Frontiers in Physiology, 2022)
Refrigerated storage of red cell concentrates before transfusion is associated with the accumulation of various alterations in red blood cells (RBC). Small RBC (type III echinocytes, sphero-echinocytes, and spherocytes) defined as storage-induced micro-erythrocytes (SME) appear during pretransfusion storage. SME accumulate with variable intensity from donor to donor, are cleared rapidly after transfusion, and their proportion correlates with transfusion recovery. They can be rapidly and objectively quantified using imaging flow cytometry (IFC). Quantifying SME using flow cytometry would further facilitate a physiologically relevant quality control of red cell concentrates. RBC stored in blood bank conditions were stained with a carboxyfluorescein succinimidyl ester (CFSE) dye and incubated at 37°C. CFSE intensity was assessed by flow cytometry and RBC morphology evaluated by IFC. We observed the accumulation of a CFSEhigh RBC subpopulation by flow cytometry that accounted for 3.3% and 47.2% at day 3 and 42 of storage, respectively. IFC brightfield images showed that this CFSEhigh subpopulation mostly contains SME while the CFSElow subpopulation mostly contains type I and II echinocytes and discocytes. Similar numbers of SME were quantified by IFC (based on projected surface area) and by flow cytometry (based on CFSE intensity). IFC and scanning electron microscopy showed that ≥95% pure subpopulations of CFSEhigh and CFSElow RBC were obtained by flow cytometry-based sorting. SME can now be quantified using a common fluorescent dye and a standard flow cytometer. The staining protocol enables specific sorting of SME, a useful tool to further characterize this RBC subpopulation targeted for rapid clearance after transfusion.